If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + (2n + 4) = 6 Reorder the terms: 2n + (4 + 2n) = 6 Remove parenthesis around (4 + 2n) 2n + 4 + 2n = 6 Reorder the terms: 4 + 2n + 2n = 6 Combine like terms: 2n + 2n = 4n 4 + 4n = 6 Solving 4 + 4n = 6 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4n = 6 + -4 Combine like terms: 4 + -4 = 0 0 + 4n = 6 + -4 4n = 6 + -4 Combine like terms: 6 + -4 = 2 4n = 2 Divide each side by '4'. n = 0.5 Simplifying n = 0.5
| 5x^3-15x^2= | | 2x+12+3x+23=180 | | 6(x-8)=8(x-10) | | 3c+9=-27 | | t^2-4-21=0 | | 22x^2-17xy+3y^2= | | P^2-6p-16=0 | | -7=1-4x+6x | | 15=5d+3d | | .5(16-2h)=1 | | 4n+n=5 | | 117=139k | | 2x+6+4x+-3=5x+12 | | 3z-2w= | | 18-c+9c+6= | | (2x-1)(x-1)=(x-5)(2x-5) | | (17b-7)-8(2b+1)=-2 | | .5x+7=3 | | (3x-2)=(9x-26) | | -7x=2(x-63) | | 3y+2y+y^2+5+y= | | 5+3m-1=9m+6-4m | | -1t+-0.4=-3.0 | | 0=-17x^2+19x | | -7y+5=-8y+2 | | 5w-6=5 | | 3(x-2)=5(x-1) | | -25(10-x)=25x+250 | | 4x*2-10x+35=0 | | 97.24=x-(x*.20) | | 3y-2=-10 | | 16=(6y+2)-(y-5)-(2y+16) |